Perubahan Segmentasi Kinerja Keuangan Pada Industri Konstruksi Untuk Akuisisi - Jerry Haikal; Apriliyanto, Dimas Rahardiyan (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The Covid 19 pandemic that occurred in 2020 hit many companies hard, one of the worst impacts is companies engaged in the construction industry. The COVID-19 pandemic poses major challenges for construction companies in Indonesia, including project delays, financial problems, and operational adjustments. One of the strategies that companies can implement so that the company can survive or even grow is to conduct mergers and acquisitions. How to determine which prospective companies in the construction industry are worth acquiring. Data from 25 issuers that have been analyzed based on several financial ratios, namely D/E Ratio, ROA, ROE, NPM, Receivables Turnover Ratio, and Current Ratio. The author groups the changes in financial performance into five clusters from Very Good (A) to Very Bad (E) using IBM SPSS version 22 by performing K-Mean Cluster Classification. The results of the analysis are that there are 7 issuers that have the best performance in the period from 2022 to 2023. Of the 7 companies, there are 2 companies that have the best performance, namely PT Fimperkasa Utama Tbk (FIMP) so that this company is very feasible to be acquired and PT Adhi Karya (Persero) Tbk which is able to maintain its performance in the Excellent Category (A). So that PT Adhi Karya (Persero) can acquire PT Fimperkasa Utama Tbk (FIMP) as its subsidiary. In addition to the increase in performance, there are 14 companies that have the same performance as the previous year and remain in the Poor (D) category, namely PT Acset Indonusa Tbk, Bukaka Teknik Utama Tbk etc. There are 3 companies that have decreased performance. There are 3 companies that have decreased performance, namely PT Bangun Karya Perkasa Jaya Tbk, PT Wijaya Karya (Persero) Tbk and PT Waskita Karya (Persero) Tbk.